WHATSAPP MESSENGER FOR EDUCATION: ATTITUDE, PERCEIVED EASE OF USE AND RETENTION LEVEL AMONG UNDERGRADUATE STUDENTS IN KWARA STATE UNIVERSITIES, NIGERIA - HAMZAT, AFEEZ ABIOLA; COKER, ADESHINA (ACADEMIA: Jurnal Inovasi Riset Akademik, 2024)
Social media usage for education can never be overemphasized as its rewards are enormous. As one of the integrated social media for education, WhatsApp messenger is an instant message application that runs on smartphone and web-based devices that enables users to trade information via various media form (Sahu, 2019). Many people seem to be awared of WhatsApp messenger and its use. This study therefore investigated the attitude, perceived ease of use and retention level of WhatsApp messenger for education among undergraduate students of Kwara State universities and as well investigated the students’ perceived ease of use of WhatsApp messenger based on school gender. The study revealed that undergraduate students’ attitude towards using WhatsApp messenger for Education in Kwara State universities is positive, the undergraduate students’ perceived ease of use of WhatsApp messenger for education is positive, the undergraduate students’ retention level in using of WhatsApp messenger for education is high, and there is no significant difference in students’ perceived ease of use of WhatsApp messenger for education based on gender. ABSTRAKPenggunaan media sosial untuk pendidikan tidak boleh terlalu ditekankan karena manfaatnya sangat besar. Sebagai salah satu media sosial terintegrasi untuk pendidikan, WhatsApp messenger merupakan aplikasi pesan instan yang berjalan pada smartphone dan perangkat berbasis web yang memungkinkan penggunanya bertukar informasi melalui berbagai bentuk media (Sahu, 2019). Banyak orang tampaknya mengetahui WhatsApp messenger dan penggunaannya. Oleh karena itu penelitian ini menyelidiki sikap, persepsi kemudahan penggunaan dan tingkat retensi WhatsApp messenger untuk pendidikan di kalangan mahasiswa S1 Universitas Negeri Kwara dan juga menyelidiki persepsi kemudahan penggunaan WhatsApp messenger oleh siswa berdasarkan gender sekolah. Studi ini mengungkapkan bahwa sikap mahasiswa sarjana terhadap penggunaan WhatsApp messenger untuk Pendidikan di Universitas Negeri Kwara adalah positif, persepsi kemudahan mahasiswa sarjana dalam menggunakan WhatsApp messenger untuk pendidikan adalah positif, tingkat retensi mahasiswa sarjana dalam menggunakan WhatsApp messenger untuk pendidikan tinggi, dan tidak terdapat perbedaan yang signifikan dalam persepsi siswa tentang kemudahan penggunaan WhatsApp messenger untuk pendidikan berdasarkan gender.